(3TQM GdedNU aj GdgjFIs - (3GdQhej, bGVj RGOg (B- (3ehSi LdHj, ehSi Hf eMeO, fMh (B840 (3g`s
(3ChdgG (B:s
(3GdMeO ddg GdPj LYd GdTeS VjGAG hGdbeQ fhQG Efg aj ReGffG gPG bO GfOQS JOQjS GdYdhe GdMbjbjI heYGde GdJYdje dGSjeG GdQjGVj ef HjfgG aEf QjGVgG bO NdJs
(3BNQgG (B:s
(3hgPg GdSfI GdbeQjI GdhSjWI fGbUI Yf GdSfI GdTeSjI GdMbjbjI HYTQI CjGe hYTQjf SGYI hfUa SGYI HGdJbQjH hGdCUhH Cf jheG HYTQI CjGe hEMOi hYTQjf SGYI HGdJbQjH Jes
(3JHUQI GdYfhGf (B:s
(3GdedNU aj GdgjFI d TQa GdOjf GdLZejfj GdNhGQRej , J (B618 (3g`s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B7\328s
(3cTa GdXfhf (B2\1819s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3Gdadc hGdJfLje hGdejbGJs